-الجزائر-الاغواط OOREDOOدور إعلانات الصحف في نجاح السياسة الترويجية للمؤسسة دراسة ميدانية بمؤسسة - بلقاسمي عبد القادر; أرزيقي علاء الدين; ساحي وسيم مصطفى (جامعة عمار ثليجي الاغواط, 2022)
Promotion is the definition of the consumer about the entire organization and its products that it offers. It is an element of the effective marketing mix that cannot be dispensed with. It also consists of a mixture called the promotional mix and among the elements of its advertising mix. It represents one of the most important elements of the promotional mix, as it is the means of communication between the institution and the consumer, which is the face that overlooks the audience, and advertising is several means, and among the advertising means is the press advertisement, where the press advertisement plays the role of mediator between the advertiser and the public. This study aims to know the role of newspaper advertisements in all its ways and types and how to design the press advertisement for the success of the promotional policy in the institution, where the success of the promotional policy must be familiar with all advertising means. The interview with the Director of Human Resources at the Ooredoo Corporation branch in Laghouat, Algeria, was a means of collecting primary data. The obtained answers and some of the institution’s documents, desk survey, were used to reach the results. The descriptive analytical approach was also used because it depends on the study of reality. It is expressed as and quality.